تأثير استخدام نموذج التّعليم التّعاوني بنوع تقديم المباراة (Make a Match) في نتائج دراسة اللّغة العربيّة لدى الطّلّاب بالمدرسة المتوسّطة الإسلاميّة الحكوميّة 3 ليما فولوه كوتا سومطرة الغربيّة - الحنيفة, روضة; رينا, أوكتا; أنس, البيهقي; حسنة, نور (EDUMALSYS Journal of Research in Education Management, 2023)
The researcher found problems in the study of the Arabic Language among the students of the eighth grade of the government Islamic school 3 lima puluh kota. Many students do not obtain study results higher than the minimum standard for the grade obtained. And their lack of interest in learning the Arabic language is because they consider the Arabic language a difficult lesson, and the teachers teaching the Arabic language still use the classical education model. The researcher uses quantitative research with the type of experimental quantitative research. As for the number of the research community, it is 288 students, and it was appointed by 72 students. As for the results of the research, there is an effect of using the cooperative education model with the type of presentation of the competition in the study of the Arabic language for students, and the extent of the effect is about 50%. The average result of the post-test in the experimental class was 74,17 and in the control class, it was 66,53. The researcher found that the significant or sig.(2-tailed) in the hypothesis test is 0,032 and this result is less than 0,05. Therefore, the payoff hypothesis and the accepted propositional hypothesis. This indicates that there is an average difference between the experimental class and the control class in the study of the Arabic language.